MENINGKATKAN AKTIVITAS DAN KETERAMPILAN PEMECAHAN MASALAH MATEMATIKA MENGGUNAKAN MODEL PRIMER DAN MEDIA KARBO DI SEKOLAH DASAR: Penelitian Tindakan Kelas - Sri Indah Utary; Ratna Purwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to describe the activity of teacher and students, while also examining enhancements improvements in problem-solving skills and student learning outcomes using a PRIMER learning models and KARBO media. This research used Classroom Action Research (CAR) and uses qualitative and quantitative methods. The participants in the research were carried out in 5th grade of SDN Belitung Utara 1 with an overall 27 students in the 2023/2024 school year. Data analysis in this research employed qualitative descriptive analysis techniques and cross tabulation, explained with tables, pictures and interpretation with percentages. The outcomes of this research show that the teacher’s activity was rated as 36 based on the criteria “Very Good”, classical student activity reached 93% with the criteria “Very Active”, classical problem-solving skills reached 96% with “Very Skilled” criteria, and student learning outcomes in the cognitive domain clasically reached 96%, clasically the affective domain reached 100%, and clasically the psychomotor domain reached 100%. Based on the findings, it can be inferred that the PRIMER learning model and KARBO media can enhance student activity, problem-solving skills, and student learning achievement.